2013
DOI: 10.1038/ijos.2013.41
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-2 gene controls tooth root development in coordination with formation of the periodontium

Abstract: Formation of the periodontium begins following onset of tooth-root formation in a coordinated manner after birth. Dental follicle progenitor cells are thought to form the cementum, alveolar bone and Sharpey's fibers of the periodontal ligament (PDL). However, little is known about the regulatory morphogens that control differentiation and function of these progenitor cells, as well as the progenitor cells involved in crown and root formation. We investigated the role of bone morphogenetic protein-2 (Bmp2) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
(56 reference statements)
2
54
1
1
Order By: Relevance
“…The Osterix ( Osx )- Cre line has been used to selectively delete floxed alleles in committed osteoblasts and odontoblasts [30, 31], though the spatiotemporal expression of Osx in the wider periodontium has not been completely resolved [32-34]. While the Osx-Cre transgene has been reported to cause delayed or defective skeletal and craniofacial mineralization resulting from Osterix loss-of-function [35-37], studies including analysis of molar teeth have not identified similar dental defects [30, 38, 39].…”
Section: Resultsmentioning
confidence: 99%
“…The Osterix ( Osx )- Cre line has been used to selectively delete floxed alleles in committed osteoblasts and odontoblasts [30, 31], though the spatiotemporal expression of Osx in the wider periodontium has not been completely resolved [32-34]. While the Osx-Cre transgene has been reported to cause delayed or defective skeletal and craniofacial mineralization resulting from Osterix loss-of-function [35-37], studies including analysis of molar teeth have not identified similar dental defects [30, 38, 39].…”
Section: Resultsmentioning
confidence: 99%
“…Some models, such as Osr2-Cre;Smad4 fl/fl and K14-Cre;Smad4 fl/fl (Huang et al, 2010), show phenotypes in early stages of tooth development, but it is hard to determine whether the root defect is secondary to the crown defect. Other models, including OC-Cre (Bae et al, 2013b;Gao et al, 2009;Kim et al, 2013;Zhang et al, 2013), Col1a1-Cre (Kim et al, 2012) and Sp7-Cre (Rakian et al, 2013;Wang et al, 2013), take effect too late, only targeting differentiated cells. Here, we used the Gli1-CreERT/loxP system to target the early progenitor cells for root development.…”
Section: Discussionmentioning
confidence: 99%
“…4). Specifically, deletion of Bmp2 in osterixpositive mesenchymal progenitor cells causes abnormal odontoblast differentiation and short roots (Rakian et al, 2013). Moreover, restriction of Bmp4 expression in the dental mesenchyme by Ring proteins, which contain a characteristic zinc-finger domain that mediates protein-protein interactions, affects odontoblast differentiation and root formation (Lapthanasupkul et al, 2012).…”
Section: Bmp/tgfβ Signalingmentioning
confidence: 99%